Pemanfaatan Kulit Buah Nanas sebagai Selai dengan Variasi Jenis Gula - Yohana Monica Larasati Parapat; Dina Mardhatilah; Sunardi Sunardi (Program Studi Teknologi Hasil Pertanian, 2025)
This study investigated the effects of different sugar types coconut, palm, and granulated sugar and their concentration ratios on the characteristics of pineapple peel jam. Using a two- factor Randomized Complete Block Design, the research found that the type of sugar significantly influenced the jam's moisture content, pH, reducing sugar levels, color, and consumer preference for its color, taste, and spreadability, though it had no effect on vitamin C content or aroma preference. Similarly, the ratio of pineapple peel to sugar was found to significantly affect the jam's moisture content, pH, color, and preference for its color, aroma, and spreadability, while having no significant impact on reducing sugar, vitamin C, or taste preference. Overall, the findings highlight the critical role that both sugar type and concentration play in determining the final quality and sensory characteristics of pineapple peel jam.